A meta-analysis and meta-regression study of the effects of Triphala on anthropometric parameters - Wiraphol Phimarn; Pawich Paktipat; Chatmanee Taengthonglang; Kritsanee Saramunee; Bunleu Sungthong (Shahrekord University of Medical Sciences, 2022)
Triphala is a medicinal plant that can improve anthropometric parameters. Although Triphala is widely used, especially in India and Thailand, its efficacy is still controversial. Consequently, the purpose of this meta-analysis and meta-regression analysis was to assess the safety of Triphala and its effects on anthropometric parameters. A comprehensive review and meta-analysis of randomized controlled trials assessing the safety of Triphala and its effects on anthropometric parameters were conducted by searching PubMed, ScienceDirect, Web of Science, and ThaiLIS databases. Two authors independently conducted the study selection and data extraction and evaluated the quality of the studies. The clinical therapeutic effects and adverse events of Triphala were evaluated and aggregated using a random-effects model. The chi-square and I2 tests were used to assess heterogeneity between the studies. Seven trials with a total of 458 patients were included. The Triphala-treated groups demonstrated a considerable decrease in body weight (BW) (weighted mean difference [WMD]: −2.99 kg; 95% CI: −5.31, −0.67; P = 0.012; I2 = 94.4%), body mass index (BMI) (WMD: −0.79 kg/m2; 95% CI: −1.52, −0.07; P = 0.032; I2 = 90.4%), and waist circumference (WC) (WMD: −1.86 cm; 95% CI: −3.10, −0.62; P = 0.003; I2 = 88.8%). During the treatment period, there were no reports of serious adverse events related to Triphala. However, there was no association between the dose or duration of treatment and any of the recorded outcomes. This meta-analysis revealed that Triphala significantly improved BW, BMI, and WC. Nevertheless, substantial, well-designed randomized controlled studies are necessary to confirm this finding.